The life of the pond - Amos, William Hopkins (New York, McGraw-Hill, 1967)
Surveys the animals and plants which bring life to the great variety of ponds in the United States.
Bibliography: p. 227.
Keywords: Freshwater ecology; Freshwater ecology; Freshwater biology; Ecology